Kesiapan Menerapkan Green Human Resource Management (GHRM) pada Kantor Kesyahbandaran dan Otoritas Pelabuhan (KSOP) Kelas 1 Palembang - M Oktarianto; Dina Mellita; Efan Elpanso; Heriyanto Heriyanto (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the readiness level of the Class I Palembang Port Authority (KSOP) in implementing Green Human Resource Management (GHRM). GHRM is an effort to integrate human resource management practices with environmental sustainability goals, which is considered important given the environmental responsibilities of the port sector. This study uses a descriptive quantitative method with a census approach to all employees of the Class I Port Authority Office in Palembang. The data is analyzed based on three aspects of GHRM: Green Training, Green Performance Management, and Green Employee Involvement. The results of the study indicate that, in general, KSOP Class I Palembang is at a high level of readiness in implementing GHRM. This readiness is reflected in the average index of the Green Training (4.217) and Green Employee Involvement (4.35) aspects, which are in the Very Ready category. Readiness in the Green Training aspect shows the effectiveness of environmental training, while Green Employee Involvement reflects the high level of active employee participation. Meanwhile, the Green Performance Management aspect (4.166) is in the Ready category, indicating that environmental elements have been accommodated in performance assessments but still need further strengthening, especially in the reward system. The conclusion of this study confirms that KSOP Class I Palembang is ready to integrate sustainability principles through GHRM practices.